2020
DOI: 10.1097/mat.0000000000001009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Socioeconomic Status on Patients Supported with Contemporary Left Ventricular Assist Devices

Abstract: Continuous-flow left ventricular assist devices (CF-LVADs) are increasingly used in advanced heart failure patients. Recent studies suggest that low socioeconomic status (SES) predicts worst survival after heart transplantation. Both individual-level and neighborhood-level SES (nSES) have been linked to cardiovascular health; however, the impact of SES in CF-LVAD patients remains unknown. We hypothesized that SES is a major determinant of CF-LVAD candidacy and postimplantation outcomes. A retrospective chart r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 25 publications
2
24
0
Order By: Relevance
“…First, this can be due to differences in listing characteristics in that those from most deprived areas were not as debilitated as those from the least which was supported by our findings, the most deprived group (Q4) had lower Patients with high psychosocial risk factors are usually younger, nonwhite and male, 19 characteristics that us and others found in the low SES LVAD receipients. 11 It may be possible that through the LVAD candidate selection process, those patients with the highest psychosocial risk factors were excluded. Thus, the LVAD selection process likely created a highly selected patient population with low SES but reduced psychosocial risk factors making it challenging to evaluate the impact of neighborhood deprivation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, this can be due to differences in listing characteristics in that those from most deprived areas were not as debilitated as those from the least which was supported by our findings, the most deprived group (Q4) had lower Patients with high psychosocial risk factors are usually younger, nonwhite and male, 19 characteristics that us and others found in the low SES LVAD receipients. 11 It may be possible that through the LVAD candidate selection process, those patients with the highest psychosocial risk factors were excluded. Thus, the LVAD selection process likely created a highly selected patient population with low SES but reduced psychosocial risk factors making it challenging to evaluate the impact of neighborhood deprivation.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with previous studies demonstrating that patients from high SES were slightly older and had lower BMI. 10,11 There is also evidence that LVAD patients who are 60 years old or older have higher incidence of HF secondary to ischemic cardiomyopathy and are at increased risk of post-LVAD death. 14 On the other hand, obesity status has shown no impact in overall LVAD survival but it increased the likelihood of readmissions.…”
Section: (C) (B)mentioning
confidence: 99%
“…Plausible explanations for this are the following: (i) surgical and post‐implantation outcomes of patients with continuous flow LVADs have improved over time, and socio‐economic status should not be considered as a risk factor for mortality. In fact, in a recent single‐centre study, lower socio‐economic status was associated with decreased risk of death in the unadjusted analysis, and the association became non‐significant after adjustment for clinically relevant comorbidities. (ii) Socio‐economic disparities are narrowing over time the role of multidisciplinary teams in identifying barriers to health‐care access, and assist with medication coverage has been crucial in the improvement of outcomes after observed in the last 20 years .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the area deprivation index had little impact on survival after LVAD implantation ( 59 ). Another study showed that low SES might not affect the clinical course after LVAD implantation ( 60 ). The readmission ratio was also not changed by the low SES ( 61 ).…”
Section: Left Ventricular Assist Devicementioning
confidence: 99%